(untitled) (Strathmore Law Journal, 2020)
As part of the ongoing movement in support of the abolition of the death penalty across the world, this article presents a selection of cases brought before the United Nations Human Rights Committee (the Committee) on violations of the right to life. With a special focus on Zambian cases, the objective is to demonstrate how the Committee’s views reflect its longstanding jurisprudence that the death penalty should only be applied in the most exceptional circumstances.